2019
DOI: 10.1167/19.9.12
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal properties of attentional selectivity for saccades and reaches

Abstract: The preparation and execution of saccades and goaldirected movements elicits an accompanying shift in attention at the locus of the impending movement. However, some key aspects of the spatiotemporal profile of this attentional shift between eye and hand movements are not resolved. While there is evidence that attention is improved at the target location when making a reach, it is not clear how attention shifts over space and time around the movement target as a saccade and a reach are made to that target. Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 75 publications
0
11
1
Order By: Relevance
“…Similar to previous studies (Hanning et al, 2018;Jonikaitis & Deubel, 2011), we found that visual attention was allocated in parallel to both effector targets during simultaneous eye-hand movement preparation. This is in contrast to previous behavioral studies observing that the eye carries more attentional weight than the hand during simultaneous eye hand movements, yielding attentional competition between the two effector systems when two separate targets have to be selected (Khan et al, 2011;Stewart, Verghese, & Ma-Wyatt, 2019). Yet, our results show that the deployment of attention towards one effector target was unaffected by the simultaneous motor preparation of the other effector system.…”
Section: Discussioncontrasting
confidence: 90%
“…Similar to previous studies (Hanning et al, 2018;Jonikaitis & Deubel, 2011), we found that visual attention was allocated in parallel to both effector targets during simultaneous eye-hand movement preparation. This is in contrast to previous behavioral studies observing that the eye carries more attentional weight than the hand during simultaneous eye hand movements, yielding attentional competition between the two effector systems when two separate targets have to be selected (Khan et al, 2011;Stewart, Verghese, & Ma-Wyatt, 2019). Yet, our results show that the deployment of attention towards one effector target was unaffected by the simultaneous motor preparation of the other effector system.…”
Section: Discussioncontrasting
confidence: 90%
“…The spatial pattern of integration benefits could also be reflective of attentional allocation to these task-relevant locations across the saccade. Whereas many studies have shown a specificity of presaccadic attention at the saccade target (Deubel and Schneider 1996; Hoffman and Subramaniam 1995; Kowler et al 1995), there is also evidence to suggest that attentional benefits may be observed at surrounding locations (Castet et al 2006; Harrison et al 2012; Stewart and Ma-Wyatt 2017; Stewart et al 2019), and that locations other than the saccade target can be attentionally selected based on both features, and the location of behaviorally relevant stimuli on previous trials (White et al 2013). This attention to task-relevant, nonsaccade targets emerges as rapidly as 30 ms after a saccade (Yao et al 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Given the assumption of independence of pre- and postsaccadic signals, the maximum possible benefit from integration is statistically limited by MLE: this method has been applied to multisensory integration (Ernst and Bülthoff 2004), where small benefits are also observed. Presaccadic attentional benefits have also been measured in a similarly small range (Li et al 2016; Rolfs and Carrasco 2012; Stewart et al 2019). Rather than integration benefits being a definitive measure of how much perceptual stability can be attributed to transaccadic integration, we think rather that these measured benefits are a hint of what might be going on in the visual system: presaccadic information and postsaccadic information are initially processed independently, and if they are attributed to the same source, then they are weighted and integrated into a single transsaccadic percept.…”
Section: Discussionmentioning
confidence: 99%
“…The deployment of visuospatial attention is tightly linked with the execution of saccadic eye movements (Awh, Armstrong, & Moore, 2006). Numerous studies have shown that shifts in attention precede eye movements, improving both the sensitivity to and discriminability of visual targets of the upcoming saccade (Stewart, Verghese, & Ma-Wyatt, 2019;Born, Ansorge, & Kerzel, 2013;Peterson, Kramer, & Irwin, 2004;Deubel & Schneider, 1996;Hoffman & Subramaniam, 1995) and promoting their entry into working memory (Hanning, Jonikaitis, Deubel, & Szinte, 2016). To what extent the neural basis of this presaccadic boost in perception, that is, overt attention, overlaps with that of covert attention has not been examined.…”
Section: Introductionmentioning
confidence: 99%